Perlindungan Data Pribadi Dalam Proses Mediasi Restorative Justice Tindak Pidana Penipuan Berbasis Digital: Analisis Yuridis Dan Filosofis John Rawls - Dedi Mustopa; Indra Yudha Koswara; Wahyu Donri Tinanbunan; Tri Setiadi (Jurnal Civic Hukum, 2026)
This article examines how personal data protection should be integrated into restorative justice (RJ) mediation in digital fraud cases through a juridical and philosophical reading of John Rawls. The study uses a normative-empirical legal approach by reviewing criminal law regulations, the Personal Data Protection Law, and practical risks faced by victims during mediation. The analysis shows a regulatory gap: RJ rules still do not expressly regulate informed consent, technical data security, the right to erasure, and liability when data leaks occur in mediation. From Rawls's justice as fairness perspective, the current model also tends to sacrifice the equal liberty of victims and fails to protect the least advantaged party, namely victims with weak digital literacy and unequal bargaining positions. Based on these findings, the article proposes a reconstruction of digital-fraud mediation through a victim-centred data protection model consisting of explicit consent, limited data access, anonymized mediation, controlled documentation, and mandatory post-mediation data deletion.